Diseases of Gastropoda - O’Brien, Michelle F.; Pellett, Sarah (Frontiers in Immunology, 2022)
Gastropods (class Gastropoda) form the largest of the classes in the phylum Mollusca and inhabit terrestrial, fresh water and marine environments. A large number of these species are of major conservation importance and are an essential component of ecosystems. Gastropods may be deemed as pests, having a negative impact in horticulture and agriculture, whereas others may be used as a food source for human consumption and therefore are beneficial. Gastropods are susceptible to primary diseases and also act as intermediate hosts for diseases which affect other animals, including humans. The diseases described include two that are notifiable to the World Organisation for Animal Health (OIE): Xenohaliotis californiensis and Abalone viral ganglioneuritis caused by Haliotid herpesvirus-1 (HaHV-1). Research into the diseases of gastropods has often focused on those species that act as intermediate disease hosts, those that are used in research or those cultured for food. In this paper we review the viral, bacterial, fungal, parasitic and miscellaneous conditions that have been reported in gastropods and mention some of the factors that appear to predispose them to disease. The pathogenicity of a number of these conditions has not been fully ascertained and more research is needed into specifying both the etiological agent and significance in some of the diseases reported.